Penerapan AI dalam Konseling Modern: Analisis tentang Peluang, Efektifitas dan Tantangan Etis - Hendradi Styawan; Budiyanto Budiyanto; Evi Winingsih (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
Introduction: The integration of Artificial Intelligence (AI) in guidance and counseling represents a digital transformation aimed at overcoming the cognitive limitations of counselors in processing complex data in real-time. This study aims to analyze implementation opportunities, clinical effectiveness, and the ethical challenges emerging from AI integration in modern counseling services. Methods: This research employs a qualitative approach using the library research method. Data were collected through a systematic review of 25 primary scientific literatures from reputable journals and recent research reports published within the last five years (2020-2025). Data analysis techniques included content analysis and thematic analysis to identify technological effectiveness and ethical parameters of AI utilization. Results: Findings indicate that AI enhances the accuracy of psychological assessments by 80-99% through Natural Language Processing (NLP) technology. Furthermore, chatbot-based interventions have been proven to increase accessibility and reduce client depressive symptoms by up to 51%. This technology enables service personalization through the continuous integration of historical data and physical metrics. Discussion: Despite its high analytical efficiency, AI is positioned as a supportive instrument that cannot replace the human therapeutic alliance. Primary challenges include data privacy, algorithmic